2009
DOI: 10.1038/cmi.2009.25
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Chemokine Receptor 9 Internalization Triggered by Interleukin 2 and Interleukin 4

Abstract: In previous study, we found that the chemokine receptor 9 (CCR9) was highly expressed on CD4 + T cells from patients with T-cell lineage acute lymphocytic leukemia (T-ALL) and mediated leukemia cell infiltration and metastasis. Combined use of interleukin 2 (IL-2) and IL-4 promoted the internalization of CCR9 and therefore attenuated leukemia cell infiltration and metastasis. In this study, we preliminarily investigated the mechanism of internalization of CCR9 on MOLT4 cell model (a human leukemia T-cell line,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…HEK293 cells or TLR9-expressing 293 cells (mTLR9/293) were plated in 24-well plates (2 ϫ 10 5 cells/well) and cotransfected with 0.25 g of pNF-kB-luc and 0.25 g of the pRL-TK internal control plasmid (Promega, Madison, WI, USA) using the PolyJet reagent (SignaGen, MD, USA) (34). After 24 h, the transfected cells were stimulated with CpG ODN, EV71, or EV71-infected cell supernatants for 24 h. The cells were then lysed so that the luciferase activity could be measured using a dual-luciferase reporter assay system (Promega Co., Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…HEK293 cells or TLR9-expressing 293 cells (mTLR9/293) were plated in 24-well plates (2 ϫ 10 5 cells/well) and cotransfected with 0.25 g of pNF-kB-luc and 0.25 g of the pRL-TK internal control plasmid (Promega, Madison, WI, USA) using the PolyJet reagent (SignaGen, MD, USA) (34). After 24 h, the transfected cells were stimulated with CpG ODN, EV71, or EV71-infected cell supernatants for 24 h. The cells were then lysed so that the luciferase activity could be measured using a dual-luciferase reporter assay system (Promega Co., Madison, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…CCR9, a member of G protein-coupled receptors, is crucial in T-cell development and for tissue-specific homing of T cells upon binding to its specific ligand CCL25 [16]. CCR9 is highly expressed in MOLT4 cells, a T-ALL cell line.…”
Section: Introductionmentioning
confidence: 99%
“…However, Zhang and collaborators have shown that IL-2, in conjunction with IL-4, promotes the internalization of CCR9 [50]. Thus, we next addressed whether RA-iTreg cells generated with APCs in the presence of TILRA up-regulated the expression of α4β7 and CCR9.…”
Section: Ra-itreg Cells Present An Unbiased Homing Potentialmentioning
confidence: 99%